APLIKASI PUPUK VERMIKOMPOS DAN POC URIN SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Solanum lycopersicum) - Yulianti Tampubolon, Melani Ratni; Utama, Putra; Muztahidin, Nur Iman; Rohmawati, Imas (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2024)
This study aimed to determine the effect of vermicompost fertilizer dose and concentration of cow urine Liquid Organic Fertilizer (LOF) on the growth and yield of tomato plants (Solanum lycopersicum). This research was an experimental study conducted from March to May 2024. The experimental design used in this study was a factorial Randomised Group Design (RGD) consisting of two factors. The first factor was the dose of vermicompost fertilizer, which consisted of 4 levels, including 0 g/plant, 35 g/plant, 45 g/plant, and 55 g/plant. The second factor was the cow urine concentration LOF, which consisted of four levels: 0 ml/l, 30 ml/l, 60 ml/l, and 90 ml/l. The results showed that the treatment with a vermicompost fertilizer dose of 45 g/plant had the best effect on the parameters of plant height at 4 weeks (79.16 cm), 5 weeks (94.58 cm), and 6 weeks (117.08 cm), and stem diameter at 4 weeks (6.00 mm), 5 weeks (7.01 mm), and 6 weeks (7.94 mm). The concentration of cow urine LOF at 60 ml/l had the best effect on the parameters of plant height at 4 weeks (78.50 cm), 5 weeks (95.66 cm), and 6 weeks (116.25 cm), the number of fruits per plant (12.83 fruits), and fruit weight per plant (474.75 g). There was an interaction between the treatment of vermicompost fertilizer dose and concentration of cow urine, with a combination of 45 g/plant of vermicompost and 60 ml/l cow urine having the best effect on the parameter of plant height 6 weeks after planting (123.33 cm).